Development of an Oral Operant Nicotine/Ethanol Co-Use Model in Alcohol-Preferring (P) Rats - Hauser, Sheketha R.; Katner, Simon N.; Deehan Jr, Gerald A.; Ding, Zheng-Ming; Toalston, Jamie E.; Scott, Briana J.; Bell, Richard L.; McBride, William J.; Rodd, Zachary A. (Alcoholism, clinical and experimental research, 2012)
Background Alcohol abuse is frequently associated with nicotine (Nic) use. The current experiments were conducted to establish an oral operant ethanol + Nic (EtOH + Nic) co‐use model and to characterize some aspects of EtOH + Nic co‐use. Methods Rats were allowed to choose between EtOH alone or EtOH + Nic solutions. Additionally, alcohol‐preferring (P) rats were allowed to concurrently self‐administer 3 distinct EtOH solutions (10, 20, and 30%) with varying amounts of Nic (0.07, 0.14, or 0.21 mg/ml) under operant conditions. P rats were also allowed to concurrently self‐administer 2 distinct amounts of Nic (0.07 and 0.14 mg/ml) added to saccharin (Sacc; 0.025%) solutions. Results During acquisition, P rats responded for the EtOH + Nic solutions at the same level as for EtOH alone, and responding for EtOH + Nic solutions was present throughout all drinking conditions. P rats also readily maintained stable self‐administration behaviors for Nic + Sacc solutions. The results demonstrated that P rats readily acquired and maintained stable self‐administration behaviors for EtOH + 0.07 and EtOH + 0.14 mg/ml Nic solutions. Self‐administration of EtOH + 0.21 mg/ml Nic was established in only 50% of the subjects. P rats readily expressed seeking behaviors for the EtOH + Nic solutions and reacquired EtOH + Nic self‐administration during relapse testing. In addition, tail blood samples indicated that EtOH + Nic co‐use resulted in pharmacologically relevant levels of both EtOH and Nic in the blood. Conclusions Overall, the results indicate that P rats readily consume EtOH + Nic solutions concurrently in the presence of EtOH alone, express drug‐seeking behaviors, and will concurrently consume physiologically relevant levels of both drugs. These results support the idea that this oral operant EtOH + Nic co‐use model would be suitable for studying the development of co‐abuse and the consequences of long‐term chronic co‐abuse.